Longitudinal changes in left ventricular structure and function in patients with type 2 diabetes: Normal weight versus overweight/obesity. (September 2019) - Kim, Seong Hwan; Sung, Ki-Chul; Lee, Seung Ku; Park, Juri; Kim, Nan Hee; Kim, Sun H; Shin, Chol
Objective: Although reported to be independent of obesity, the longitudinal changes of left ventricular structure and function have not been well characterized in normal-weight individuals with type 2 diabetes compared with overweight/obese individuals with type 2 diabetes. Methods: A total of 558 participants in the Korean Genome and Epidemiology Study who underwent tissue Doppler echocardiography at baseline (cycle 4) and after 8 years (cycle 8) were classified into three groups based on body mass index and diabetes status: (1) normal-weight individuals without type 2 diabetes, (2) normal-weight individuals with type 2 diabetes and (3) overweight/obese individuals with type 2 diabetes. Results: Only overweight/obese individuals with type 2 diabetes group had higher adjusted left ventricular mass index and lower tissue Doppler imaging early diastolic velocity and E/Em ratio compared with the normal-weight individuals without type 2 diabetes group at baseline and after 8 years. Participants in overweight/obese individuals with type 2 diabetes group also showed the higher prevalence and odds of left ventricular hypertrophy (16.0%; adjusted odds ratio: 2.24; 95% confidence interval: 1.22–5.06) and left ventricular diastolic dysfunction (49.1%; 3.45; 1.01–4.32). Among participants with normal left ventricular structure and function at baseline, only overweight/obese individuals with type 2 diabetes group was associated with greater incidence of left ventricular hypertrophy (relative risk: 2.28; 1.04–4.98) over 8 years but not diastolic dysfunction. Conclusion: Cross-sectional and longitudinal observations suggest that increasing body mass index category and its associated metabolic abnormalities at baseline are associated with an increased risk for left ventricular hypertrophy and greater impairment in left ventricular diastolic parameters.